Pedagogies innovations for Sustainable development: educational intervention based on the natural and cultural heritage topics in the English language class. - Peralta Cedeño, Arianna Stefania; Macías Villalva, Karoline Nicole; VILLAFUERTE, JHONNY (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This article aims to contribute to the innovations of pedagogies for sustainable development since English language class. This research adscript to the postmodern paradigm and the mixed approach of the socio-educational research. The research team designed an educational intervention that combines topics related to natural and cultural Ecuadorian heritage with flipped classrooms and Content and Language Integrated Learning methodologies. The participants are 23 people; 9 instructors and 14 students between 12 and 48 years old. The research instruments were: the Likert scale questionnaire, created by the University of San Pedro in Peru, to assess students’ motivations for practicing the English language; a knowledge rubric to evaluate students’ listening skills, and focus groups on collecting participants’ opinions about the educational intervention introduced in this research process. The results show significant changes in the student’s motivation for practicing the English language but not in listening skills. It concluded that there were no correlations between the factors students’ motivation for practicing the English language and listening skills when the educational intervention uses natural and cultural topics.